Toward a conceptual understanding of the flow experience in elite athletes - Jackson, S. A. (Research Quarterly for Exercise and Sport, 1996)
An indepth investigation into flow state was conducted in order to understand how this optimal state is expertenced by elite athletes. Twenty-eight elite-level athletes, representing 7 sports, were interviewed on their perceptions of flow state during performance of their sport. Csikszentmihalyi s (1990) model of the flow state was examined for its applicability to elite athletes. Correspondence was found between the dimensions of flow, as desscribed by Csikszentmihalyi (1990), and the athletes`descriptions of their experience of flow; some dimensions received greater support through the qualitative analysis of the athletes ` descriptions than did other dimensions. Those dimensions of flow most represented across the ,group`s data were the autotelic experience of flow, total concentration on the task at hand, merging of action and awareness, and the paradox of control. The analyses provided a detailed, sport-specific picture of flow state in elite athletes.